Changes in inflammatory factors, oxidative stress, glucose and lipid metabolism, and insulin resistance in patients with polycystic ovary syndrome - Zhong, Peiwen; Guan, Baoxing; Lin, Yanting; Zhang, Siyou (Cellular and Molecular Biology, 2022)
Polycystic ovary syndrome (PCOS) is a common disease in women, affecting women's menstruation and significantly impacting women's physical and mental health. Studies have shown that insulin resistance has an important relationship with polycystic ovary. It is of great significance to explore the changes of inflammatory factors, oxidative stress, glucose and lipid metabolism, and insulin resistance in patients with PCOS. In the study process, 642 polycystic ovary patients in the first half of 2019 were divided into insulin resistance (n=357) and non-insulin resistance (n=285) groups. Oxidative stress index, glucose, and lipid metabolism index, and inflammatory factors were detected during the study process. The results showed that the levels of hs-CRP, TNF- α, and IL-6 in the IR group were 5.9mg/L, 9.2μg/L, and 87.2ng /ml, while those in the non-IR group were 4.6mg/L, 6.3μg/L and 51.5ng/ml, respectively. Thus, IL-6 and insulin levels maintain a dynamic balance. Low levels of IL-6 can promote insulin secretion, while high levels can inhibit its secretion. The results of this study will provide a specific clinical reference value for the prevention and treatment of polycystic ovary syndrome.